Rapid recovery of depleted abalone in Isla Natividad, Baja California, Mexico. Issue 3 (23rd March 2022) - Smith, Alexandra; Aguilar, Juan Domingo; Boch, Charles; De Leo, Giulio; Hernández‐Velasco, Arturo; Houck, Stephanie; Martinez, Ramón; Monismith, Stephen; Torre, Jorge; Woodson, C. Brock; Micheli, Fiorenza
Abstract: In the last decades, many marine invertebrates have experienced dramatic declines throughout many coastal marine ecosystems worldwide due to overfishing, disease outbreaks, and climate vulnerability. Despite extensive conservation and restoration effort, evidence of successful population recovery is rare. In this work, we document mass mortality events of pink and green abalone ( Haliotis corrugata and Haliotis fulgens ) in 2009–2010, and their subsequent rapid recovery following the continued enforcement and monitoring of two voluntary no‐take reserves by the local fishing cooperative (2006–present) and a 6‐year fishing closure (2012–2017) around Isla Natividad, Baja California Sur, Mexico. Age data collected from harvested abalone in 2019 suggest recruitment was maintained throughout the years when abundance was lowest following mass mortalities. The observed 6 to 8‐year time frame for recovery is consistent with scenarios presented in previous modeling studies, where marine reserves and other measures aimed at protecting large spawners predicted the potential for rapid recovery of abalone populations. This case study supports the effectiveness of a portfolio of resilience strategies, which include combining climate refugia and marine reserves, adherence to conservative annual fishing quotas, fishing closures, minimum size limitations, and ecological monitoring. Importantly, this example showcases how close collaboration between fishers, resource managers, scientists, and non‐governmental organization (NGOs) is critical for designing, implementing, and learning from conservation and management interventions to reverse marine population and ecosystem decline, reinforcing the legacy of Dr. Pete Peterson's life work on fully integrating ecology with marine management and restoration.